MODERN TREATMENT OPTIONS OF TOENAIL ONYCHOMYCOSIS (A LITERATURE REVIEW) - Marina M. Tlish; Marina E. Shavilova (Кубанский научный медицинский вестник, 2019)
Introduction. The importance of investigating the problem of toenail onychomycosis is associated not only with its widespread prevalence among the population and negative effects on the patient life quality, but also with signifi cant diffi culties arising during its therapy. At the moment, a large number of systemic and local antifungal drugs are successfully applied for treating this pathology. Moreover, new physiotherapeutic methods are being developed and introduced into clinical practice. These treatment approaches are based on different action mechanisms, thus demonstrating certain advantages and disadvantages.Discussion. This article sets out to provide a review of antifungal drugs recommended for use in the Russian Federation in patients suffering from onychomycosis of the feet. The results of studies aimed at establishing the clinical effi cacy and application of azole, allylamine, morpholine and ciclopirox derivatives are summarized. Criteria for the selection of these drugs for systemic and local therapy are given. Both Russian and foreign recent publications devoted to physical factors in the treatment of fungal nail infections are analyzed. The action mechanisms, clinical effi cacy, application methods, signifi cant adverse effects of laser and photodynamic methods, as well as ultrasound, magnetic and electric fi elds, are described.Conclusion. Modern approaches to the treatment of toenail onychomycosis are shown to use a large selection of systemic and local antifungal drugs, as well as physiotherapeutic methods for correcting this pathology. All of them have different action mechanisms characterized by particular advantages and disadvantages. To date, there is no universal drug for the treatment of toenail onychomycosis, which would affect all parts of the mycotic process. Following the analysis of recently published literature, it is shown that the use of topical medications and physiotherapy in combination not only signifi cantly reduces the duration of the application of systemic antimycotic drugs, but also expands the etiological indications and their adverse effects. Therefore, such a therapy is established to be the most effective approach to the treatment of toenail onychomycosis at the present stage.